Subcarpathian Voivodship on the Electoral Map of Poland (1989-2014) - Szczepański, Dominik (Political Preferences, 2015)
The aim of the article was to present electoral activities diversification as well as political preferences of the citizens of the Subcarpathian Voivodeship in years 1989-2014. The measure of the conducted analyses were the results of parliamentary and European Parliament elections, by means of which it was possible to indicate recurring cyclicality of right-wing political sympathies of the citizens of the Subcarpathian Voivodeship, as well as noticable, with regards to the whole country, election turnout. The primary part of the conducted analysis was an attempt to answer the question of what determined the change of political preferences and if contemporary electoral activity and political sympathies reflect historical and cultural determinants. Key words: Subcarpathian Voivodeship, elections, electoral, political parties